2023
DOI: 10.51984/jopas.v22i2.2788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carburizing Temperature and Post Carburizing Treatments on Microhardness and Microstructural Evolution of Carburized Low-Carbon Steel

Mohamed Ali Ballem,
Mustafa M. Aldarwish,
Abdulhamid S. Aljuroushi
et al.

Abstract: This paper reports the results of an experimental investigation of the effect of carburizing temperature and post carburizing heat treatments on the structural and hardness properties of pack carburized low-carbon steel. The carburizing processes were performed at temperatures of 900°C and 1035°C for 6 hours. After that, two hardening procedures were carried out. In the first hardening procedure, the specimens were directly quenched in oil from carburizing temperatures, while in the second procedure, a double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, the carburizing process can be tailored to achieve specific mechanical properties by carefully controlling various parameters, such as temperature, time, and carbon potential. Many studies have examined the influence of temperature variations on the carbonitriding process of low-carbon steels due to their significance in the manufacturing industry [27,28]. Additionally, studies have shown that longer carburizing times can lead to increased case depth and higher carbon content at the surface, resulting in enhanced hardness and wear resistance [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the carburizing process can be tailored to achieve specific mechanical properties by carefully controlling various parameters, such as temperature, time, and carbon potential. Many studies have examined the influence of temperature variations on the carbonitriding process of low-carbon steels due to their significance in the manufacturing industry [27,28]. Additionally, studies have shown that longer carburizing times can lead to increased case depth and higher carbon content at the surface, resulting in enhanced hardness and wear resistance [29,30].…”
Section: Introductionmentioning
confidence: 99%